The sleepwalker - Bohjalian, Chris, 1962- (Doubleday, 2017)
When a sleepwalker who has experienced episodes of near violence while unconscious goes missing, her eldest daughter, Lianna, finds herself drawn to a lead detective who seems to know more than he is revealing.